FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENJUALAN - Kristi, Ronny Januar; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out price, product quality and service variables to the sales level. The respondents are the customers who have purchased Honda motorcycle and 100 respondents have been selected as samples, the observation periods were conducted in 2014. The data is the primary data and the secondary data. The primary data is observation and questionnaires. The secondary. Research method in this research is quantitative; linear regressions analysis is used as the analysis technique. The instrument in this research is questionnaires which are issued to the customers who have purchased Honda motorcycle at PT. Daya Anugrah Mandiri Surabaya. The result of the research is shows that price variables has positive and significant influence to the sales level which means that price which has been offered by the company is relatively low and affordable for the customers so its sales level increases, product quality variable has positive and significant influence to the sales level which means that when the quality of product which is demanded by the customer is getting better, the sales level is getting high as well, and service variable has positive and significant influence to the sales level which means that when the service which has been provided by the company to the customer is getting better, it will increase the revenue of the company, and the variable which has dominant influence to the sales level is service.Keywords: price, product quality, service and sales level